AB2 type hydrogen storage alloy with long service life as well as preparation method and application of AB2 type hydrogen storage alloy

By adding FeNb alloy into the AB2 type hydrogen storage alloy matrix and controlling the particle size, the problems of uneven component distribution and impurities are solved, and a higher hydrogen storage capacity and longer cycle life are achieved.

CN119800196APending Publication Date: 2025-04-11GANJIANG INNOVATION ACAD CHINESE ACAD OF SCI
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411945012.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-27
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

During the preparation process, the existing AB2 type hydrogen storage alloys are prone to uneven distribution of components and the introduction of impurities, resulting in a decrease in the amount and life of hydrogen storage.

Method used

The FeNb alloy is incorporated into the TiaZr(1-a)CrbMn(2-b) matrix, and its particle size is controlled, and the lattice constant of the alloy is adjusted to improve the hydrogen storage capacity and structural stability.

Benefits of technology

It achieves higher hydrogen storage capacity and longer cycle life, and improves the alloy's circulation capacity retention rate and anti-hydrogen absorption expansion and hydrogen release shrinkage.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005213433660000081
    Figure BDA0005213433660000081
  • Figure BDA0005213433660000091
    Figure BDA0005213433660000091
Patent Text Reader

Abstract

The invention discloses a long-life AB2 type hydrogen storage alloy as well as a preparation method and application thereof, and relates to the technical field of hydrogen storage alloys. According to the AB2 type hydrogen storage alloy with the long service life, a small amount of FeNb alloy is doped into a TiaZr (1-a) CrbMn (2-b) alloy matrix, meanwhile, the particle size of the TiaZr (1-a) CrbMn (2-b) alloy matrix is controlled, the hydrogen storage and release capacity of the hydrogen storage alloy is improved due to the particle size of 100-300 microns, regulation and control over crystal lattice parameters of the alloy matrix are achieved due to introduction of the intermediate alloy, and the service life of the alloy is prolonged. Therefore, the obtained alloy has high hydrogen storage and release capacity and high capacity retention ratio, the hydrogen storage alloy has the hydrogen storage capacity of 1.85 wt% or above under the hydrogen pressure of 5 MPa, the effective hydrogen absorption capacity of 1.80 wt% or above, and the capacity retention ratio of 91% or above can still be kept after long-term hydrogen absorption and release circulation.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of hydrogen storage alloys, and in particular to a long-life AB2 type hydrogen storage alloy and a preparation method and application thereof. Background Art

[0002] As an efficient hydrogen storage technology, hydrogen storage alloys can store a large amount of hydrogen in the form of metal hydrides with high hydrogen storage density. This material has the characteristics of selective absorption of hydrogen, can efficiently separate and purify hydrogen, and the released hydrogen is of high purity. The hydrogen absorption and desorption process of hydrogen storage alloys is reversible, which makes them reusable and has good cycle stability. In addition, hydrogen storage alloys release heat when absorbing hydrogen and absorb heat when releasing hydrogen. This characteristic makes them have application potential in thermal energy storage and conversion. At the same time, hydrogen storage alloys are also highly safe because hydrogen is stored in hydrogen storage alloys in the form of atoms rather than molecules, which reduces the risks during storage and transportation. In summary, hydrogen storage alloys have great application potential in the field of hydrogen energy with their high hydrogen storage density, selective absorption, high purity release, reversible cycle, safety and environmental friendliness.

[0003] However, the existing AB2 type hydrogen storage alloys are usually prepared by arc melting and high-frequency induction melting, which easily lead to uneven distribution of components and easy introduction of impurities during the preparation process, which leads to a decrease in the hydrogen storage capacity and life of the hydrogen storage alloy. How to improve the hydrogen storage capacity and life of AB2 type hydrogen storage alloys is an urgent problem that restricts the current development of hydrogen storage alloys. Summary of the invention

[0004] In order to solve the shortcomings of the prior art, the present invention provides a long-life AB2 type hydrogen storage alloy. a Zr (1-a) Cr b Mn (2-b) FeNb alloy is added to the alloy matrix, and its particle size is controlled to adjust the alloy lattice constant, so that the hydrogen storage alloy has a higher hydrogen storage and desorption capacity, and the alloy crystal structure is stable, with a longer cycle life and a higher cycle capacity retention rate.

[0005] Another object of the present invention is to provide a method for preparing a long-life AB2 type hydrogen storage alloy.

[0006] Another object of the present invention is to provide an application of a long-life AB2 type hydrogen storage alloy.

[0007] The above-mentioned purpose of the present invention is achieved through the following technical solutions:

[0008] A long-life AB2 type hydrogen storage alloy, the long-life AB2 type hydrogen storage alloy is Ti a Zr(1-a) Cr b Mn (2-b) Fe c Nb d , where 0.7≤a≤0.8, 0.6≤b≤0.7, 0.04≤c≤0.08, 0.02≤d≤0.06;

[0009] The average particle size of the long-life AB2 type hydrogen storage alloy is 100 to 300 μm.

[0010] The long-life AB2 type hydrogen storage alloy provided by the present invention is a Zr (1-a) Cr b Mn (2-b) FeNb alloy is doped into the matrix (AB2 type, in which part of the Ti sites are replaced by Zr, and part of the Mn sites are replaced by Cr). By controlling the particle size of the alloy, the proportion of each component in the matrix, the composition of the doped alloy and its doping amount, an AB2 type hydrogen storage alloy with higher hydrogen storage and desorption capacity and cycle capacity retention rate is obtained. Specifically, due to the adjustment of the particle size of the alloy, the microstructure of the alloy is significantly refined, and the increase in the number of grain boundaries promotes the diffusion of hydrogen, so that the hydrogen storage and desorption capacity of the alloy is improved. However, the lattice of the alloy is prone to structural changes (hydrogen absorption expansion, dehydrogenation contraction) during the hydrogen storage and desorption process. In order to improve the structural stability of the alloy, the present invention adds FeNb alloy to the alloy matrix, adjusts the lattice constant of the alloy, and makes the crystal structure of the alloy stable, has a better ability to resist hydrogen absorption expansion and hydrogen desorption contraction, and is not prone to structural collapse under the condition of long-term hydrogen storage and desorption cycles, so it has a longer cycle life and a higher cycle capacity retention rate.

[0011] In a specific embodiment of the present invention, by a Zr (1-a) Cr b Mn (2-b) The matrix is ​​doped with FeNb50(Fe 0.62 Nb 0.38 )、FeNb60(Fe 0.52 Nb 0.48 )、FeNb70(Fe 0.42 Nb 0.58 ) to adjust the two parameters c and d.

[0012] Preferably, the bulk density of the long-life AB2 type hydrogen storage alloy is 2.5-4 g / cm 3 .

[0013] The smaller the bulk density, the smaller the particle size of the prepared alloy, and satellite powder is easily generated during the alloy preparation process, resulting in poor hydrogen storage performance of the alloy; the larger the bulk density, the larger the particle size of the prepared alloy, and the internal structure of the obtained alloy is easily transformed from cellular crystals to dendrites due to the reduced cooling rate, which also leads to poor hydrogen storage performance of the alloy.

[0014] Preferably, the crystal structure of the long-life AB2 type hydrogen storage alloy is C14 Laves phase.

[0015] More preferably, the lattice constant of the long-life AB2-type hydrogen storage alloy is 0.49 to 0.495 nm.

[0016] If the lattice constant is too large, the hydrogen absorption capacity of the alloy is high but the hydrogen desorption platform pressure is low, resulting in low hydrogen desorption capacity of the alloy; if the lattice constant is reduced, the hydrogen absorption platform pressure of the alloy is high, resulting in low hydrogen absorption capacity and thus low hydrogen desorption capacity.

[0017] Preferably, the long-life AB2 type hydrogen storage alloy has a maximum hydrogen absorption capacity of >1.8wt% under a hydrogen pressure of 5MPa, a capacity retention rate of >90% after 100 cycles, and a hydrogen desorption platform pressure of 0.2-0.4MPa at room temperature.

[0018] The present invention also provides a method for preparing a long-life AB2 type hydrogen storage alloy, comprising the following steps:

[0019] The raw materials are mixed according to the element ratio in the composition of the long-life AB2 type hydrogen storage alloy, and smelted at a temperature of 1800°C to 2500°C. After obtaining the melt, the melt is impacted with gas at a pressure of 3 to 10 MPa for an impact time of ≥ 200 seconds. After solidification, the long-life AB2 type hydrogen storage alloy is obtained.

[0020] The present invention adopts a gas atomization method to prepare a long-life AB2 type hydrogen storage alloy. As a new type of powder making technology, the gas atomization method combines the alloy smelting and powder making processes into one, and mainly includes three steps of smelting, gas atomization, and solidification. In the gas atomization step, the melt after high-frequency induction smelting is injected into the tundish. As the melt flows out of the tundish in a thin stream, high-pressure gas is sprayed from the nozzle at its outlet, making the melt into fine droplets. The droplets fall in the spray tower and solidify into powder, which is collected at the bottom of the tower.

[0021] In a specific embodiment of the present invention, the preparation method of the long-life AB2 type hydrogen storage alloy is carried out in a water-cooled wall copper crucible vacuum suspension smelting gas atomization metal powder making equipment. When preparing the long-life AB2 type hydrogen storage alloy of the present invention in the above-mentioned water-cooled wall copper crucible vacuum suspension smelting gas atomization metal powder making equipment, the mixed raw materials in the present invention are first melted into liquid metal, and the liquid metal forms droplets under the impact of the gas, and the powdered long-life AB2 type hydrogen storage alloy can be obtained after the droplets solidify.

[0022] Controlling the gas impact time in the present invention is actually controlling the atomization time. The atomization time can affect the solidification state and nucleation and growth of the powder, and further affect the particle size and distribution, physical properties, etc. of the powder. In the present invention, the atomization time should be ≥200s. Too short atomization time may result in the metal droplets not being fully broken, resulting in uneven distribution of powder particle size, affecting the subsequent application performance of the powder; insufficient atomization time may also result in the inability to form a good non-equilibrium eutectic phase (i.e., alloy) between the powders, thereby affecting purity and performance; too short atomization time may also result in the powder not being fully cooled and solidified, thereby affecting the yield of the alloy.

[0023] The preparation method provided by the present invention also controls the pressure of gas atomization. This is because excessive atomization pressure will cause the secondary crushing degree of metal droplets to increase, and a large number of fine metal droplets will be formed. Under the action of high-speed airflow, they are easy to adhere to large-sized droplets that are not completely solidified, thereby forming satellite powder, resulting in uneven distribution of components. At the same time, excessive atomization pressure may also lead to the production of hollow powder, which will also lead to uneven distribution of components; a larger atomization gas pressure can obtain a higher airflow velocity, but an excessive airflow velocity will lead to serious gas waste and may be unfavorable for the uniform distribution and cooling of the powder. However, too low atomization pressure will also lead to a decrease in the performance of the resulting alloy. Under a lower atomization pressure, the impact of the airflow on the metal melt is not severe enough, resulting in incomplete crushing; a lower atomization pressure may lead to a lower yield of fine powder, because a lower pressure is not conducive to the generation of small-particle powder; a lower or higher atomization gas pressure will lead to a decrease in the loose density and fluidity of the powder, affecting the subsequent processing and application of the powder. In addition, the present invention also controls the smelting temperature. This is because if the smelting temperature is too high, the metal melt is easily oxidized and some alloy elements are burned out. However, if the temperature is too low, the metal melt is difficult to fully melt, resulting in some elements being unable to be incorporated into the alloy.

[0024] In a specific embodiment of the present invention, the gas is an inert gas, and more specifically, the gas includes argon.

[0025] Preferably, the smelting temperature is 1900-2200°C.

[0026] Preferably, the pressure of the gas is 3-4 MPa.

[0027] Preferably, the impact time is 500-700s.

[0028] Too long atomization time will increase the contact time between the powder and the gas environment, thereby increasing the possibility of oxidation and affecting the purity and performance of the powder; too long atomization time may also cause excessive cooling of the powder and affect the microstructure of the powder.

[0029] In a specific embodiment of the present invention, the smelting is carried out in an inert gas atmosphere. More specifically, the inert gas is argon.

[0030] The present invention also protects the application of a long-life AB2 type hydrogen storage alloy in the field of hydrogen storage.

[0031] Compared with the prior art, the present invention has the following beneficial effects:

[0032] The hydrogen storage alloy provided by the present invention has a hydrogen storage capacity of more than 1.85wt% under a hydrogen pressure of 5MPa, an effective hydrogen absorption capacity of up to 1.80wt%, a capacity retention rate of more than 91% after 100 cycles, and a hydrogen release platform pressure of more than 0.25MPa at 25°C. DETAILED DESCRIPTION

[0033] The present invention is further described below in conjunction with specific embodiments, but the embodiments do not limit the present invention in any form. Unless otherwise specified, the raw materials and reagents used in the embodiments of the present invention are conventionally purchased raw materials and reagents.

[0034] Example 1

[0035] A long-life AB2 type hydrogen storage alloy Ti 0.7 Zr 0.3 Cr 0.6 Mn 1.4 Fe 0.06 Nb 0.04 The average particle size of the long-life AB2 type hydrogen storage alloy is 200 μm, and the bulk density is 3 g / cm 3 , the crystal structure is C14 Laves phase.

[0036] The preparation method of the long-life AB2 type hydrogen storage alloy in this embodiment comprises the following steps:

[0037] The raw materials are mixed according to the proportion of elements in the composition of the long-life AB2 type hydrogen storage alloy (Fe and Nb elements are added in the form of FeNb50 alloy, and the remaining elements are added as metal single substances), and smelted at a temperature of 2000°C. After obtaining the melt, the melt is impacted with argon gas at a pressure of 3.5 MPa for 600 seconds. After solidification, the long-life AB2 type hydrogen storage alloy is obtained.

[0038] Example 2

[0039] A long-life AB2 type hydrogen storage alloy, which differs from Example 1 only in that:

[0040] Add FeNb60 alloy (alloy is Ti 0.7 Zr 0.3 Cr 0.6 Mn1.4 Fe 0.05 Nb 0.05 ), the average particle size of the long-life AB2 type hydrogen storage alloy is 200 μm, and the bulk density is 3 g / cm 3 .

[0041] The preparation method of the long-life AB2 type hydrogen storage alloy in this embodiment is consistent with that in Example 1.

[0042] Example 3

[0043] A long-life AB2 type hydrogen storage alloy, which differs from Example 1 only in that:

[0044] Add FeNb70 alloy (alloy is Ti 0.7 Zr 0.3 Cr 0.6 Mn 1.4 Fe 0.04 Nb 0.06 ), the average particle size of the long-life AB2 type hydrogen storage alloy is 200 μm, and the bulk density is 3 g / cm 3 .

[0045] The preparation method of the long-life AB2 type hydrogen storage alloy in this embodiment is consistent with that in Example 1.

[0046] Example 4

[0047] A long-life AB2 type hydrogen storage alloy, which differs from Example 1 only in that:

[0048] c = 0.08, d = 0.05, i.e., more FeNb50 alloy is added;

[0049] The average particle size of the long-life AB2 type hydrogen storage alloy is 200 μm and the bulk density is 3 g / cm 3 .

[0050] The preparation method of the long-life AB2 type hydrogen storage alloy in this embodiment is consistent with that in Example 1.

[0051] Example 5

[0052] A long-life AB2 type hydrogen storage alloy, which differs from Example 1 only in that:

[0053] c = 0.03, d = 0.02, i.e., the amount of FeNb50 alloy added is even less;

[0054] The average particle size of the long-life AB2 type hydrogen storage alloy is 200 μm and the bulk density is 3 g / cm 3 .

[0055] The preparation method of the long-life AB2 type hydrogen storage alloy in this embodiment is consistent with that in Example 1.

[0056] Example 6

[0057] A long-life AB2 type hydrogen storage alloy, which differs from Example 1 only in that:

[0058] In the preparation method of the long-life AB2 type hydrogen storage alloy in this embodiment, the pressure of argon gas is 10 MPa. The average particle size of the long-life AB2 type hydrogen storage alloy prepared in this embodiment is 100 μm, and the bulk density is 3.5 g / cm 3 .

[0059] Example 7

[0060] A long-life AB2 type hydrogen storage alloy, which differs from Example 1 only in that:

[0061] In the preparation method of the long-life AB2 type hydrogen storage alloy in this embodiment, the melting temperature is 1800°C.

[0062] The average particle size of the long-life AB2 type hydrogen storage alloy prepared in this embodiment is 220 μm, and the bulk density is 3.2 g / cm 3 .

[0063] Example 8

[0064] A long-life AB2 type hydrogen storage alloy, which differs from Example 1 only in that:

[0065] In the preparation method of the long-life AB2 type hydrogen storage alloy in this embodiment, the melting temperature is 2500°C.

[0066] The average particle size of the long-life AB2 type hydrogen storage alloy prepared in this embodiment is 240 μm, and the bulk density is 3.4 g / cm 3 .

[0067] Comparative Example 1

[0068] An AB2 type hydrogen storage alloy, wherein the difference from Example 1 is only that:

[0069] Composition: Ti 0.7 Zr 0.3 Cr 0.6 Mn 1.4 Nb 0.04 , that is, no Fe element is added (the raw material in the alloy preparation process is replaced by Nb element from FeNb50 alloy). The average particle size of the AB2 type hydrogen storage alloy obtained in this comparative example is 200 μm, and the bulk density is 3 g / cm 3 .

[0070] The preparation method of the AB2 type hydrogen storage alloy in this comparative example is consistent with that in Example 1.

[0071] Comparative Example 2

[0072] An AB2 type hydrogen storage alloy, wherein the difference from Example 1 is only that:

[0073] Composition: Ti 0.7 Zr 0.3 Cr 0.6 Mn 1.4 Fe 0.02 Nb 0.01 The average particle size of the AB2 type hydrogen storage alloy obtained in this comparative example is 200 μm, and the bulk density is 3 g / cm 3 .

[0074] The preparation method of the AB2 type hydrogen storage alloy in this comparative example is consistent with that in Example 1.

[0075] Comparative Example 3

[0076] An AB2 type hydrogen storage alloy, wherein the difference from Example 1 is only that:

[0077] Composition: Ti 0.7 Zr 0.3 Cr 0.6 Mn 1.4 Fe 0.09 Nb 0.06 The average particle size of the AB2 type hydrogen storage alloy obtained in this comparative example is 200 μm, and the bulk density is 3 g / cm 3 .

[0078] The preparation method of the AB2 type hydrogen storage alloy in this comparative example is consistent with that in Example 1.

[0079] Comparative Example 4

[0080] An AB2 type hydrogen storage alloy, wherein the difference from Example 1 is only that:

[0081] In the preparation method of the AB2 type hydrogen storage alloy in this comparative example, the pressure of argon gas is 12 MPa.

[0082] The average particle size of the AB2 type hydrogen storage alloy obtained in this comparative example is 180 μm, and the bulk density is 3.2 g / cm 3 .

[0083] Comparative Example 5

[0084] An AB2 type hydrogen storage alloy, wherein the difference from Example 1 is only that:

[0085] In the preparation method of the AB2 type hydrogen storage alloy in this comparative example, the pressure of argon gas is 2 MPa.

[0086] The average particle size of the AB2 type hydrogen storage alloy obtained in this comparative example is 400 μm, and the bulk density is 2.5 g / cm 3 .

[0087] Comparative Example 6

[0088] An AB2 type hydrogen storage alloy, wherein the difference from Example 1 is only that:

[0089] In the preparation method of the AB2 type hydrogen storage alloy in this comparative example, the impact time is 100 s.

[0090] The average particle size of the AB2 type hydrogen storage alloy obtained in this comparative example is 450 μm, and the bulk density is 2 g / cm 3 .

[0091] Comparative Example 7

[0092] An AB2 type hydrogen storage alloy, wherein the difference from Example 1 is only that:

[0093] In the preparation method of the AB2 type hydrogen storage alloy in this comparative example, the melting temperature is 1300°C.

[0094] Comparative Example 8

[0095] An AB2 type hydrogen storage alloy, wherein the difference from Example 1 is only that:

[0096] In the preparation method of the AB2 type hydrogen storage alloy in this comparative example, the melting temperature is 2800°C.

[0097] The average particle size of the AB2 type hydrogen storage alloy obtained in this comparative example is 400 μm, and the bulk density is 2.6 g / cm 3 .

[0098] Performance Testing

[0099] Lattice constant test: The alloy sample is crushed and ground to obtain alloy powder, and the alloy powder is subjected to XRD ray diffraction and GSAS refinement to obtain the lattice constant. According to the test, the lattice constants of the long-life AB2 type hydrogen storage alloys obtained in Examples 1 to 8 of the present invention are all 0.49 to 0.495 nm.

[0100] 5MPa maximum hydrogen absorption test: refer to national standard GB / T 33291-2016, and test at 25℃.

[0101] Effective hydrogen absorption test: Tested in accordance with the national standard GB / T 33291-2016, with a cut-off pressure of 0.1MPa or above.

[0102] 100 cycle capacity retention test: refer to national standard GB / T 33291-2016, 25℃, test at 5MPa.

[0103] 25℃ Hydrogen degassing platform pressure test: refer to national standard GB / T 33291-2016, and test at 5MPa.

[0104] The specific test data are shown in Table 1 below:

[0105] Table 1. Specific test data of alloys obtained in Examples and Comparative Examples

[0106]

[0107]

[0108] According to the data in Table 1 above, it can be seen that the hydrogen storage alloy provided by the present invention has a hydrogen storage capacity of more than 1.85wt% under a hydrogen pressure of 5MPa, an effective hydrogen absorption capacity of up to 1.80wt%, a capacity retention rate of more than 91% after 100 cycles, and a hydrogen desorption platform pressure of more than 0.25MPa at 25°C.

[0109] According to the data of Comparative Examples 1 to 3, a Zr (1-a) Cr b Mn (2-b) An inappropriate amount of FeNb alloy added to the matrix or only adding Nb alone will lead to a decrease in the performance of the alloy prepared using the same gas atomization powder making technology. This may be because the amount of alloy added is inappropriate or only adding Nb alone results in an inappropriate lattice constant.

[0110] According to the data of Comparative Examples 4 to 5, it can be seen that excessive or insufficient atomization pressure will also lead to reduced performance of the resulting alloy. This is because inappropriate atomization pressure makes it difficult for the alloy to form powder with a suitable particle size.

[0111] According to the data of Comparative Example 6, when the impact time during the gas atomization process is too short, that is, the gas atomization time is too short, the powder is not fully broken, and thus the alloy performance decreases.

[0112] According to the data of Comparative Examples 7 to 8, when the smelting temperature is too low, the powder-making raw materials cannot form liquid for atomization, and thus the alloy cannot be produced; when the smelting temperature is too high, Mn in the alloy volatilizes, the alloy platform pressure is significantly reduced, and the amount of hydrogen released is reduced.

[0113] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.

Claims

1. A long-life AB2 type hydrogen storage alloy, characterized in that: The long-life AB2 type hydrogen storage alloy is Ti a Zr (1-a) Cr b Mn (2-b) Fe c Nb d , where 0.7≤a≤0.8, 0.6≤b≤0.7, 0.04≤c≤0.08, 0.02≤d≤0.06; The average particle size of the long-life AB2 type hydrogen storage alloy is 100 to 300 μm.

2. The long-life AB2 type hydrogen storage alloy according to claim 1, characterized in that: The bulk density of the long-life AB2 type hydrogen storage alloy is 2.5-4 g / cm 3 .

3. The long-life AB2 type hydrogen storage alloy according to claim 1, characterized in that: The crystal structure of the long-life AB2 type hydrogen storage alloy is C14 Laves phase.

4. The long-life AB2 type hydrogen storage alloy according to claim 3, characterized in that: The lattice constant of the long-life AB2 type hydrogen storage alloy is 0.49-0.495 nm.

5. The long-life AB2 type hydrogen storage alloy according to claim 1, characterized in that: The maximum hydrogen absorption capacity of the long-life AB2 type hydrogen storage alloy under a hydrogen pressure of 5MPa is greater than 1.8wt%, the capacity retention rate after 100 cycles is greater than 90%, and the hydrogen release platform pressure at room temperature is 0.2-0.4MPa.

6. The method for preparing the long-life AB2 type hydrogen storage alloy according to any one of claims 1 to 5, characterized in that: The steps include: The raw materials are mixed according to the element ratio in the composition of the long-life AB2 type hydrogen storage alloy, and smelted at a temperature of 1800°C to 2500°C. After obtaining the melt, the melt is impacted with gas at a pressure of 3 to 10 MPa for an impact time of ≥ 200 seconds. After solidification, the long-life AB2 type hydrogen storage alloy is obtained.

7. The method for preparing the long-life AB2 type hydrogen storage alloy according to claim 6, characterized in that: The smelting temperature is 1900-2200°C.

8. The method for preparing the long-life AB2 type hydrogen storage alloy according to claim 6, characterized in that: The pressure of the gas is 3-4 MPa.

9. The method for preparing the long-life AB2 type hydrogen storage alloy according to claim 6, characterized in that: The impact time is 500 to 700 seconds.

10. Application of the long-life AB2 type hydrogen storage alloy according to any one of claims 1 to 5 in the field of hydrogen storage.